Thermal analysis of magnetized TiO2-PAO nanolubricant flow in the presence of non-uniform heat source and activation energy - Bibi, Asia; Hashmi, M. S.; Riaz, Muhammad; İnç, Mustafa; Mohd Kasim, Abdul Rahman; Zainal, Nurul Amira (Springer, 2026)
In this paper, thermal properties of magnetized TiO2-PAO nanolubricant flow over a flat surface is examined. Incorporating titanium dioxide ( TiO2) NFs into a conventional polyalphaolefin (PAO) lubricant has shown much higher thermal conductivity and therefore better heat transfer capabilities, resulting in less friction, wear, and use of less energy by the mechanical system. The current discussion examines the principle of HT when subjected to both the effects of TR and non-uniform heat source. Also, the effects of local thermal non-equilibrium conditions and porous media in the optimization of HT are studied. Thermal and flow characteristics of the effect of activation energy are also taken into consideration. The nonlinear PDEs are reduced to a system comprising of ODEs through suitable STs. The MATLAB bvp4c solver is implemented to get numerical solutions. The dependence of important physical parameters on velocity, temperature distribution, and HT rate variation is shown graphically and in tabular form. Findings have shown that augmenting magnetic field strength and inertial parameters has a tremendous effect on reducing the flow of a nanolubricant. On the other hand, the existence of TR and heat generation inside the nanolubricant greatly improves the thermal performance of the lubricant. This study offers valuable results on how nanolubricants can be made more efficient and gives possible use in the automotive, aerospace, and industrial thermal management systems, which are facing dire challenges in lubrication, heat transfer as well as material performance.
Keywords: TiO2-PAONanolubricant; Non-uniform heat source; Thermal radiation (TR); Activation energy (AE); Nanofluid (NF); Heat transfer (HT); Similarity transformations (STs)